Integrating sustainability thinking and practices into surfing events: case studies in Hawaii and Jeffreys Bay - Nguyen, Tina (Department of Environmental and Geographical Science, 2018)
Sustainable surfing events are a recent phenomenon and there is little to no academic literature reflecting this development. Sustainable event management (SEM) is the integration of sustainability principles and practices into event production to produce an event that goes beyond economic longevity and fulfils important social, cultural, and environmental roles that people value. This research explores the current practices and issues surrounding the implementation of SEM into surfing events held in Hawaii, USA and in Jeffreys Bay, South Africa. The thesis follows a qualitative case study approach using semi-structured interviews, participant observation and documentary evidence. Findings demonstrated that the key obstacles to implementing sustainable event management principles and practices include limited access to capital, lack of government support, resistance to change, the absence of a common vision, and a lack of education and awareness. This study revealed the importance of context in a hosting community's journey towards sustainable event production. Overcoming these obstacles requires engagement of the private sector, influence of local champions, involvement of NGOs, trusting relationships between local and external event stakeholders, access to technology and resources, and the strategic use of media to promote sustainability awareness to all event stakeholders. Based on these findings, recommendations for improving the sustainability performance of surfing events include the development of a formal policy, education and training for event staff, a media campaign focused on sustainability issues, and in-depth engagement with the local hosting community. How the enabling or inhibiting factors play out on the ground depends on the variety of factors previously highlighted. In practice, there are linkages across SEM practices and many work in concert to enhance the overall sustainability performance. Theoretically, the implications of this research lie in its contribution to a growing body of knowledge pertaining to the surfing industry's transition towards more sustainable business operations. Practically, this information can be used to inform policy, set goals, carefully examine alternatives, establish effective factors to enable SEM, and encourage sustainable decision-making and actions. Other surfing communities can learn from the experiences of the event stakeholders in Hawaii and Jeffreys Bay to improve their efforts of hosting a sustainable surfing event. Overall, this knowledge can promote a more balanced dissemination of sustainability thinking and practices within the global surfing events sector.